Electronic structure, elastic, mechanical, thermodynamic and thermoelectric investigations of Mn2PtX (X=Rh, Pd) Heusler alloys. (March 2019) - Duan, Jinying; Yin-Wei, Wang; A-Peng, Zhang; Liu, Shoufa; Dar, Sajad Ahmad
Abstract: In the present paper, we have engaged ab-initio density functional theory within the full-potential linearized plane wave method to investigate Heusler alloys Mn2 PtX (X = Rh, Pd) for electronic structure, mechanical stability, thermodynamic and thermo-electronic possessions. Combined spin polarized generalized gradient approximation (GGA) and Hubbard correlation (GGA + U) approaches have been used to predict equilibrium structural parameters, electronic structure, mechanical, thermodynamic and thermo-electronic properties. The structural investigation reveals cubic F4-3m (216) space group as the stable ground state phase. The electronic structure results in both GGA and GGA + U present metallic nature in both spin up and down states. The calculated values of elastic constants are found to follow mechanical stability criteria in both the compounds. The mechanical results present ductile nature with high degree of anisotropy for Mn2 PtPd and brittle nature for Mn2 PtRh. We have also computed the temperature dependence of electrical conductivity, Seebeck coefficient, thermal conductivity and power factor in spin up and down states for both compounds. The Seebeck coefficient shows that electrons are charge carriers in spin up states and holes in spin down states for both compounds. Furthermore we have investigated the thermodynamic belongings like specific heat at constant volume (Cv ), Grüneisen parameter (γ), Debye temperature ( θ D ) etc. of the material. Highlights: First theoretical prediction on physical properties of Mn2 PtX (X = Rh, Pd) Heusler alloys. Electronic structure presents metallic nature with unsymmetrical band structure in spin up and down states. Further to know industrial application mechanical properties have been calculated. Thermodynamic investigation has been carried within quasi-harmonic Debye model. We have also computed the thermoelectric parameters like electrical conductivity and power factor for these materials.